Socjologia dzieciństwa: dyskusja nad pozycją dziecka w socjologii - Albański, Łukasz (Studia Edukacyjne, 2020)
This article addresses the issue of constructing childhood sociologically. Classical sociology focused on the transformation of children into reliable adult social actors, namely on the process of socialization. In contrast, the sociology of childhood, as a relatively young branch of the discipline, is sensitive to the place of children in society. Therefore, the sociology of childhood explores the very idea of the child rather than treats the child as a being with a relatively determined trajectory. The article presents sociology’s conceptual base and its different approaches to the child. In particular, the central concepts of the childhood sociology are outlined and critically discussed.